Using Virtual Learning Environment as a Medium of Instruction in EFL Context: College Teachers’ Attitudes - Liqaa Habeb Al-Obaydi (Intensive Journal, 2020)
Virtual learning is a kind of learning that is mainly web-based e-learning platform. It needs online portfolios, learning management system, systematic use of assessment, and course content in order to provide students with regular feedback. The present study deals with Iraqi college teachers’ attitudes towards using virtual learning as a medium of instruction in EFL teaching context. It attempts to see college teachers’ opinions concerning exchanging the traditional face to face teaching by totally online virtual courses. To gain the aim of the study, a questionnaire of two parts that is constructed by the researcher is used. Fifty college teachers have been chosen randomly to represent the main study sample. Based on the results gained, specific conclusions and implications are put forward.